Pathogenesis-related protein genes involved in race-specific all-stage resistance and non-race specific high-temperature adult-plant resistance to Puccinia striiformis f. sp. tritici in wheat - Sumaira Farrakh; Meinan Wang; Xianming Chen (Journal of Integrative Agriculture)
Interactions of the stripe rust pathogen (Puccinia striiformis f. sp. tritici) with wheat plants activate a wide range of host responses. Among various genes involved in the plant-pathogen interactions, the expressions of particular pathogenesis-related (PR) protein genes determine different defense responses. Different types of resistance have been recognized and utilized for developing wheat cultivars for resistance to stripe rust. All-stage resistance can be detected in seedling stage and remains at high levels throughout the plant growth stages. This type of resistance is race-specific and not durable. In contrast, plants with only high-temperature adult-plant (HTAP) resistance are susceptible in seedling stage, but become resistant when plants grow older and the weather becomes warmer. HTAP resistance controlled by a single gene is partial, but usually non-race specific and durable. The objective of this study was to analyze the expression of PR protein genes involved in different types of wheat resistance to stripe rust. The expression levels of 8 PR protein genes (PR1, PR1.2, PR2, PR3, PR4, PR5, PR9 and PR10) were quantitatively evaluated at 0, 1, 2, 7 and 14 days after inoculation in single resistance gene lines of wheat with all-stage resistance genes YrTr1, Yr76, YrSP and YrExp2 and lines carrying HTAP resistance genes Yr52, Yr59, Yr62 and Yr7B. Races PSTv-4 and PSTv-37 for compatible and incompatible interactions were used in evaluation of PR protein gene expression in wheat lines carrying all-stage resistance genes in the seedling-stage experiment while PSTv-37 was used in the HTAP experiment. Analysis of quantitative real-time polymerase chain reaction (qRT-PCR) revealed that all of the PR protein genes were involved in the different types of resistance controlled by different Yr genes. However, these genes were upregulated at different time points and at different levels during the infection process among the wheat lines with different Yr genes for either all-stage resistance or HTAP resistance. Some of the genes were also induced in compatible interactions, but the levels were almost always higher in the incompatible interaction than in the compatible interaction at the same time point for each Yr gene. These results indicate that both allsalicylic acid and jasmonate signaling pathways are involved in both race-specific all-stage resistance and non-race specific HTAP resistance. Although expressing at different stages of infection and at different levels, these PR protein genes work in concert for contribution to different types of resistance controlled by different Yr genes.